The effects of rapid urbanization on forest landscape connectivity in Zhuhai city, China - Cui, Nan; Feng, Chen-Chieh; Wang, Dan; Li, Jianfei; Guo, Luo (MDPI, 2018)
Urban forests can provide the necessary ecosystem services for their residents and play an important part in improving the urban environment. Forest landscape connectivity is a vital indicator reflecting the quality of the ecological environment and ecological functions. Detecting changes in landscape connectivity is, therefore, an important step for providing sound scientific evidence for the better urban planning. Using remote sensing images of a study area in Zhuhai City in 1999, 2005, 2009 and 2013, the dynamic forest landscape connectivity of Zhuhai city can be evaluated based on a graph-theoretic approach. The aims of our study were to discover and interpret the effect of rapid urbanization on forest landscape connectivity. The construction of ecological corridors helps us specifically compare the landscape connectivity of three parts of urban forests. On the basis of functional landscape metrics, the correlation of these metrics and patch area was discussed in order to comprehensively identify the key patches. The analysis showed that the total areas of forestlands reduced from 1999 to 2009 and then increased from 2009 to 2013, and the same trend was found in overall forest landscape connectivity. To improve the overall landscape connectivity, construct urban ecological network and appropriately protect biodiversity in the future, the existing important patches with large areas or key positions should be well protected. This study revealed that urbanization reduced the area of key patches and consequently reduced the forest landscape connectivity, which increased while the patch areas increased due to the environmental protection policy. Functional connectivity indicators could provide more comprehensive information in the development of environmental protection strategies.